Collateral Damage: The impact of Australian asylum seeker policy on Christmas Islanders (2001-2011) - Briskman, Linda; Fiske, Lucy; Dimasi, M. (Southern Cross Univeristy, Australia, 2012)
Since the Tampa incident in 2001, Christmas Island has been a central site where Australia’s border protection and asylum seeker policies are visible This article takes four key events over a ten year period to track the impact on Christmas Islanders and on the Islanders’ changing attitudes towards asylum seekers, detention and federal government policies. The views of Christmas Islanders are not often heard in public discourse about detention on the island. This article seeks to provide a platform for a snapshot of views and to call for a greater role for Islanders in decisions that profoundly affect their lives.